2012
DOI: 10.1002/chem.201103554
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of n‐ and p‐Type Reduced Graphene Oxide Transistors with the Same Molecular Backbone

Abstract: Play the field: A field‐effect transistor using reduced graphene oxides was prepared through the reduction of graphene oxides connected between two electrodes. The use of pyrene with an electron‐withdrawing group and an electron‐donating group showed the p‐ and n‐doping effects, respectively, while the pyrene backbone with no electron‐withdrawing or ‐donating groups showed no doping effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Chemical doping has been developed as it has some advantages such as a facile doping process and an ease of finding dopants. Chemical doping is easily achieved by using spin‐ or dip‐coated chemical species, including various acids, metal chlorides, and other molecules …”
Section: Introductionmentioning
confidence: 99%
“…Chemical doping has been developed as it has some advantages such as a facile doping process and an ease of finding dopants. Chemical doping is easily achieved by using spin‐ or dip‐coated chemical species, including various acids, metal chlorides, and other molecules …”
Section: Introductionmentioning
confidence: 99%
“…In continuation of this research program, we have now turned our attention to graphene materials as solid supports for catalysts bearing polyaromatic fragments, well‐known antennae that promote strong aromatic π‐π stacking and therefore fixing on the graphene surface . It has recently been disclosed that a substituent on the pyrene fragment can affect the conductivity of the graphene material . We reasoned that with a relatively close metal center, such electronic flux could affect its catalytic performance, particularly in transformations involving an electrophilic metallocarbene .…”
Section: Introductionmentioning
confidence: 67%
“…In other words, the catalytic activity of 1 is enhanced when it is supported on rGO, the adsorption leading to a decrease in electron density at the metal center. This proposal finds support in a recent contribution by Lee and co‐workers, who demonstrated that substituents on a pyrene ring induce a variation in the conductivity of graphene due to electron transfer to or from pyrene. In our case, the ‐CH 2 ‐O‐NHC substituent must act as an electron‐donating group, increasing the electron density at graphene with a corresponding decrease at the copper complex (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the absence of band gap around the Fermi level, numerous approaches have been developed using molecular doping to tailor the transport properties of graphene‐based devices for nano‐electronic and photonic applications . More generally the chemical functionalization of graphene is crucial for a variety of technological applications including novel electronics or spintronic devices, photodetectors, catalysis, molecular sensors, field‐effect transistors, new energy materials, or novel hybrid species with original properties . In this context, the noncovalent functionalization based on π –π stacking is usually preferred to covalent treatments which may degrade the aromaticity of the carbon surface by creating sp 3 carbon defects, thus, lowering the high carrier mobility …”
Section: Introductionmentioning
confidence: 99%